Yield and Physicochemical Properties of Candlenut Oil by Microwave Assisted Extraction - Shintawati Shintawati; Yatim R Widodo (CHEMICA: Jurnal Teknik Kimia, 2022)
Candlenut (Aleurites moluccana L) is one of the native plants of Indonesia, used as a spice and in the cosmetic industry. Candlenut seeds contain high oil content with unstable properties at high temperatures. Generally, candlenut oil production is carried out by direct heating and on a laboratory, scale using Soxhlet extraction with chemical solvents. Microwave heating has been widely used to extract the active compounds in plant materials. The study of candlenut oil extraction with microwaves is still limited. This study aims to identify the physicochemical properties and yield of candlenut oil extracted using the Microwave Assisted Extraction (MAE) method and compare it with solvent extraction. This research was conducted by varying the extraction time of 35 minutes, 70 minutes and 105 minutes. The results showed that candlenut oil produced by the MAE method had a density, refractive index, ALB content and saponification number of 0.867 g/ml, 1.477, 2.8085% and 212.9764 mgKOH/g sample with a yield of 38.50%.